Online purchasing: the role of web experience factors - Salleh, Noor Akma Mohd; Che Ha, Norbani; Kitchen, Philip J.; Any, Amrul Asraf Mohd (Inderscience, 2019)
This paper examines the effect of web experience factors such as usability, interactivity, trust and aesthetics derived from flow theory on purchasing intention. From 360 questionnaires distributed, 300 responses were gathered. Using logistic regression analysis, results indicate that usability, interactivity and trust are positively and significantly associated with purchasing intention whereas aesthetics is not. It seems that online retailers should adopt a targeted aesthetics approach in developing a web store depending on the type of merchandise and the markets approached. As such, retailers can lure new customers, retain existing ones and improve their attitudes toward web stores. Copyright © 2019 Inderscience Enterprises Ltd.